Analysis of Language Rules in the Description Text of Class V SDN 2 Karang Bayan Students for the 2021/2022 Academic Year - I Ketut Widiada; Muhammad Tahir; Laura Rinjani (Politeknik Siber Cerdika Internasional, 2024)
This study aims to describe the use of language rules in the description text of grade V students of SDN 2 Karang Bayan for the 2021/2022 school year. The subjects of this study were class V students consisting of 16 male students and 12 female students. The object of this study are sentences on the student's description text. The data collection technique used is documentation of the results of student description texts written individually. The type of research used is descriptive qualitative, which is research that aims to describe data in the form of description text related to the linguistic rules of description text with words clearly and in detail. Data processing used by researchers is reading all student description texts, marking errors by coding, grouping data according to the type of error, describing errors, and correcting errors. The results of this study show that the use of linguistic rules in student description texts includes 11 aspects, including nouns, adjectives, transitive verbs, adverbs, standard and non-standard words, connotations and denotations, self-created words, the use of capital letters, word writing, punctuation writing, and figurative language. The use of linguistic rules in student description texts is categorized as very low because it reaches a percentage of 44%. This means that there are still many students who are wrong in using language rules when writing. Meanwhile, the use of inappropriate language rules reached a percentage of 56%. Most students do not apply the rules when writing, especially in writing student description texts. The most common mistakes made by students on the use of capital letters and punctuation writing. Indications that cause errors occur because they are still affected by everyday language and students' inaccuracy after the end of sentences using appropriate punctuation marks so that students do not pay attention to good and correct language rules.